Pengaturan Perlindungan Hukum bagi Penyandang Disabilitas dalam Rekruitmen Calon Pegawai Negeri Sipil Dari Perspektif Hak Asasi Manusia - Nazifah, Nazifah (Legalitas: Jurnal Hukum, 2023)
Indonesia is a country based on Pancasila and the 1945 Constitution of the Republic of Indonesia which respects and upholds human dignity. Article 53 of Law Number 8 of 2016 concerning Persons with Disabilities provides high expectations for persons with disabilities that they have the same opportunities as other normal people to get a job when in reality not all employment opportunities provide equal opportunities for persons with disabilities, so this article only provide facultative justice, the impact of which is that it is difficult for persons with disabilities to find work and even if they do find work, it is not uncommon for persons with disabilities to be discriminated against in the workplace. The recruitment of candidates for civil servants (CPNS) for persons with disabilities is a manifestation that every citizen has the right to have equal opportunities in government to implement the principle of equality. Although there are already formations for people with disabilities, they have not provided equal space and justice for all types of disabilities. There are a number of requirements for applicants with disabilities in certain institutions where the criteria for disabilities that can apply are being able to see, hear and speak well, then also be able to move using a walking aid other than a wheelchair. This discriminatory requirement will clearly close the opportunity for the blind, deaf, speech impaired and physically disabled to participate in the selection of CPNS admissions. Article 45 of Law Number 8 of 2016 concerning Persons with Disabilities, which stipulates that the Government and Regional Governments are required to ensure a fair and non-discriminatory process of recruitment, acceptance, job training, job placement, work continuity, and career development and without discrimination to Persons with Disabilities. discrimination, all persons with disabilities have equal opportunities, what will determine later is the competence and capability of each during the selection process. Therefore, it is necessary to interpret the laws and regulations on future concepts and ideas related to legal protection for persons with disabilities in the recruitment system for prospective civil servants from a human rights perspective.